2009
DOI: 10.1016/j.ultsonch.2008.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-promoted synthesis of novel dispirocyclic frameworks from aza-Claisen rearrangements of Baylis–Hillman amines

Abstract: A novel tetracyclic frameworks of dispiropyrrolizidines can be obtained in moderate to good yields via the 1,3-dipolar cycloaddition of azomethine ylides with dipolarophiles derived from aza-Claisen rearrangement of Baylis-Hillman amines. The transformations are highly regioselective and stereoselective, affording the desired compounds in reduced time and increased yields under ultrasound irradiation at room temperature. All the products are confirmed by 1H, 13C NMR, IR and MS spectra, while their molecular st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…As was introduced in section , decarboxylation is a relatively mild and powerful strategy for the generation of semistabilized 2-azaallyl anions. Similarly, the tandem iminium condensation/thermal decarboxylation reaction manifold (via carboxylic acids 278 , Scheme ) is a popular method for in situ preparation of N -alkyl azomethine ylides. In 1993, Prato and co-workers demonstrated that C 60 could be converted to the corresponding pyrrolidine by 1,3-dipolar cycloaddition with the N -methyl azomethine ylide generated via thermal decarboxylation of the iminium formed by condensation between sarcosine ( N -methlyglycine) and formaldehyde (Scheme ). This so-called “Prato reaction”, and variations thereof, have since been applied toward the functionalization of fullerenes, graphene and single-walled carbon nanotubes and nanohorns, …”
Section: Azomethine Ylidesmentioning
confidence: 99%
“…As was introduced in section , decarboxylation is a relatively mild and powerful strategy for the generation of semistabilized 2-azaallyl anions. Similarly, the tandem iminium condensation/thermal decarboxylation reaction manifold (via carboxylic acids 278 , Scheme ) is a popular method for in situ preparation of N -alkyl azomethine ylides. In 1993, Prato and co-workers demonstrated that C 60 could be converted to the corresponding pyrrolidine by 1,3-dipolar cycloaddition with the N -methyl azomethine ylide generated via thermal decarboxylation of the iminium formed by condensation between sarcosine ( N -methlyglycine) and formaldehyde (Scheme ). This so-called “Prato reaction”, and variations thereof, have since been applied toward the functionalization of fullerenes, graphene and single-walled carbon nanotubes and nanohorns, …”
Section: Azomethine Ylidesmentioning
confidence: 99%